Analisis Kemampuan Pemecahan Masalah Berdasarkan Teori Polya dalam Menyelesaikan Soal Cerita Materi SPLDV Pada Siswa Kelas IX SMPN 6 Mataram TA 2022/2023 - Mia Fikjayanti; Nyoman Sridana; Eka Kurniawan; Baidowi Baidowi (Pendidikan Matematika FKIP Universitas Mataram, 2023)
This research aims to describe the problem-solving ability in math word problems of the material of the system of linear equations with two variables for ninth-grade students of SMPN 6 Mataram in the academic year of 2022/2023 with high, medium, and low problem-solving abilities. This research is a descriptive-qualitative and quantitative type, using a test of problem-solving ability and interviews as research instruments. The sample consisted of 38 ninth-grade students of SMPN 6 Mataram, selected using purposive sampling. After selecting one class, a test of problem-solving ability was given, consisting of two-word problems, followed by an interview for each criterion of problem-solving ability test results. Data analysis technique was based on the results of the math problem-solving test, divided into three criteria: high, medium, and low. The results showed that (1) the problem-solving ability of ninth-grade students of SMPN 6 Mataram in solving math word problems of the material of the system of linear equations with two variables with high criteria had an average score of 85.3, (2) the problem-solving ability of ninth-grade students of SMPN 6 Mataram in solving math word problems of the material of the system of linear equations with two variables with medium criteria had an average score of 62.8, and (3) the problem-solving ability of ninth-grade students of SMPN 6 Mataram in solving math word problems of the material of the system of linear equations with two variables with low criteria had an average score of 31.9.